Gambaran Kondisi Rumah Sehat Pada Balita Penderita Infeksi Saluran Pernapasan Akut (ISPA) Di Wilayah Kerja Puskesmas Kupang Kota Tahun 2026 (STIKES Columbia Asia Medan, 2026)
Acute Respiratory Infection (ARI) is one of the main causes of morbidity and mortality among children under five years old worldwide, especially in developing countries including Indonesia. Poor housing conditions such as inadequate ventilation, high occupancy density, humidity, and insufficient lighting may increase the risk of ARI in children. This study used a descriptive observational method. The population consisted of all toddlers suffering from ARI in the working area of Kupang Kota Health Center in 2025 totaling 911 cases. The sample consisted of 91 houses of toddlers with ARI determined using the Slovin formula. The results showed that several houses of toddlers with ARI did not meet healthy housing requirements, particularly in terms of occupancy density, ventilation, humidity, and lighting. The condition of healthy housing for toddlers suffering from ARI in the Kupang Kota Health Center working area has not fully met environmental health standards.